Arteriovenous malformation of external ear and temporal region: a case report - Gupta, Richa; Agrawal, Anil (International Journal of Research in Medical Sciences, 2017)
Arteriovenous malformations (AVMs) of the scalp are remarkably rare. We report a case of 20 years old female complaining of swelling over right pinna and scalp since 2 years with known history of trauma. This case report represents pathogenesis, clinical features and management of the disease.